(untitled) (REVISTA NODO, 2019)
La Rambla, one of the most famous streets in the world, is a pedestrian street in the heart of historic Barcelona. It’s trace separates Ciutat Vella district in two Gótico and Raval. Those neigbourhoods stand side by side as distant in social origin as near at destination: the merchandise city. In La Rambla vices and virtues of both converge. On one hand the Gothic, theme park of Catalan Middleages. It’s a kind of simulacrum created almost ex-profeso throughout the twentieth century to add monumentality to this Mediterranean city, but also to create a Catalan identity and a narrative based on architecture. It must be one of the most photographed neighborhoods in the world. On the other hand, Raval. The urban black beast, whose original name was “El Chino”. Traditional hiding place in the center of the city with everything that bourgeoisie does not want to see: whores, pimps, junkies, immigrants, poverty. Always threatened by processes of social cleansing and in recent years, by gentrification. Like pincers, in La Rambla turistification and social cleansing come together, creating a breeding ground, paradoxical and explosive, which has made this space the central place of the conflict between various groups of street workers and the Barcelona City Council. Street artists, musicians, street beer vendors, human statues, but above all “manteros”, which is the subject that occupies us in this article, have been persecuted, blackmailed, co-opted, with the ultimate goal of expelling them out of the streets or at less hide them. African migrants, mostly Senegalese, those street vendors have organized themselves politically into a “sui generis” union as a way to make their situation visible and defend their rights. This exploratory work studies the act of “putting” a blanket on the ground as a particular type of material culture that crisscrosses objects, urban infrastructures, symbols, forms of sociability and political organization “at the street level”